Diversification Strategy: Theory and Practice in Go-Jek Indonesia - Anggriani Alamsyah (Jurnal Manajemen Bisnis, 2023)
This study is analyzing successful diversification of the application-based transport company PT. Gojek Indonesia, by examining theory and practice in order to strengthen understanding of diversification strategies in business. This is a descriptive study that was conducted using observations, literature studies and an analysis of social media. The researcher first determined Gojek’s diversification strategy, then analyzed the community’s response in order to assess the success of this approach. This case study was then used to examine theories of diversification. Findings. Gojek is one of the two leading application-based transport companies in Indonesia and its diversification was successful because it built on the company’s foundation in technology and application-based services. The company prioritized three core values in its diversification strategy: speed, innovation, and social impact. This approach was successful because it was carefully considered, based on the company’s core business, and supported by diversification theory.